2009
DOI: 10.1001/archgenpsychiatry.2009.83
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Association Study of Alcohol Dependence

Abstract: Context Identification of genes contributing to alcohol dependence will improve our understanding of the mechanisms underlying this disorder. Objective To identify susceptibility genes for alcohol dependence through a genome-wide association study (GWAS) and follow-up study in a population of German male inpatients with an early age at onset. Design The GWAS included 487 male inpatients with DSM-IV alcohol dependence with an age at onset below 28 years and 1,358 population based control individuals. The fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
318
4
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 367 publications
(339 citation statements)
references
References 89 publications
8
318
4
7
Order By: Relevance
“…We also show association results (Table S4) from our study for the SNPs recently reported in the independent GWAS of alcoholdependent men by Treutlein and colleagues (24). Only one SNP, rs13160562, shows modest evidence of replication [0.88; 95% confidence interval (CI) 0.78-0.99, P = 0.03].…”
Section: Resultssupporting
confidence: 69%
See 4 more Smart Citations
“…We also show association results (Table S4) from our study for the SNPs recently reported in the independent GWAS of alcoholdependent men by Treutlein and colleagues (24). Only one SNP, rs13160562, shows modest evidence of replication [0.88; 95% confidence interval (CI) 0.78-0.99, P = 0.03].…”
Section: Resultssupporting
confidence: 69%
“…Their top two findings, rs7590720 and rs1344694, were not associated with alcohol dependence in our study in our primary analysis or in secondary analyses stratified by ancestry and sex. In comparing our findings for the top 15 signals reported by Treutlein et al (24), our results modestly support one finding, rs13160562 in the endoplasmic reticulum aminopeptidase 1 (ERAP1) gene (metaanalysis OR = 0.83, 95% CI 0.77-0.90, P = 2.74 × 10 −6 ).…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations